Analisa Thermoelectric Generator (TEG) Sebagai Penghasil Listrik Dengan Variasi Media Pendingin Air Dan Tanah - Dhimas Satria; Dwinanto Dwinanto; Arif Octa Arisandi; Imron Rosyadi; Rina Lusiani; Erny Listijorini (Metal: Jurnal Sistem Mekanik dan Termal)
The energy produced by the Sun is heat energy and light energy. One of the uses of solar thermal energy is the thermoelectric generator (TEG). This research on solar thermoelectric generators uses 2 variations of cooling media, namely water cooling media and soil cooling media with a series series for thermoelectrics, while what will be analyzed is the amount of power from both tests and the ability the solar collector absorbs the sun's radiation heat. The test results and calculations determine the calorific value of solar radiation that is absorbed by the collector. That is 25,265 Watts. As for the results of testing the cooling media, the best results were obtained for the water cooling media with the greatest value at 0.04 Watt.